Design considerations for a novel shape-memory-plate osteosynthesis allowing for non-invasive alteration of bending stiffness. (November 2017) - Krämer, Manuel; Müller, Christian W.; Hermann, Maike; Decker, Sebastian; Springer, André; Overmeyer, Ludger; Hurschler, Christof; Pfeifer, Ronny
Abstract: Biomechanical stimuli play a major role in fracture healing. Changing the fixation stiffness through the course of healing might accelerate bone healing and prevent healing complications. Shape memory alloy (SMA) based implants were developed to allow for non-invasive stiffness alteration during the fracture healing process. To gain a deeper understanding of the implant functionality based on the alloy characteristics and geometric design, the mechanical properties of different shape memory alloys where mechanically characterized. SMA bone plates were manufactured and the structural bending stiffness of the implants was determined at different temperatures and configurations. The temperature required for complete recovery of shape after deformation increased continuously with increasing pseudo-plastic deformation in SMA probes. Full recovery was observed at temperatures ranging from 38 °C to 52 °C after pseudo-plastic deformations ranging from 0.2% to 1.0% outer fibre strain, respectively. The small fragment inverse-dynamisation implants revealed bending stiffnesses ranging from 0.09 N m 2 to 0.34 N m 2 in the initial state and from 0.16 N m 2 to 0.46 N m 2 after shape alteration. Dependent on the design, a relative gain of the implant stiffness ranging from 18.8% to 115.0% could be observed. The large inverse-dynamisation implants revealed bending stiffnesses from 3.7 N m 2 to 7.1 N m 2 before and 4.1 N m 2 to 12.6 N m 2 after triggering the shape memory effect. Dependent on the design a gain in stiffness from 11.8% to 117.2% was observed. Warming the SMA implant to 40 °C for a short period of time, leads to a moderate increase in implant stiffness of up to 64.5%, while triggering the implant with 50 °C leads to a maximum increase in stiffness of up to 127.3%. The Nitinol shape memory bone plates have a huge potential for improving the treatment of long shaft fractures by allowing for the increase, decrease or incremental change of implant stiffness in fracture stabilization. However, the interaction between design, material properties, and manufacturing processes need to be carefully considered for each specific application to achieve optimum function of SMA-based, stiffness altering, fracture-fixation implants. Highlights: We have designed an implant which allows for non-invasive stiffness alteration. The large fragment implants allow for a maximum increase in stiffness of 117%. Stiffness of the shape memory implants can be incrementally triggered. Young's modulus alteration to increase the effect in inverse dynamisation implants. Pseudo-plastic deformation influences characteristic temperatures of the SME.